Assessment of in-situ tidal marsh erodibility under high flow velocities - van den Berg, M.; Rikkert, S. J. H.; Aarninkhof, S. G. J.; Labeur, R. J. (Frontiers in Environmental Science, 2024)
Coastal flood risk is expected to increase due to climate change and population growth. Much of our coastlines is protected by 'grey' infrastructure such as a dike. Dike maintenance and strengthening requires ever increasing capital and space, putting their economic viability in question. To combat this trend, more sustainable alternatives are explored, also known as Nature based Solutions. A promising option has shown to be tidal marshes. Tidal marshes are coastal wetlands with high ecological and economic value. Also, they protect dikes through wave attenuation and in case of a dike breach reduce its development. However, the effectiveness of a tidal marsh on reducing dike breach development rates highly depends on the stability of the tidal marsh itself. Not much is known about the stability of a tidal marsh under dike breach conditions, which are accompanied with flow velocities that can reach 4-5 m s -1 . In this study we tested the vegetation response and erodibility of a mature tidal marsh, in-situ, under high flow velocities (>0.5 m s -1 ). Our results confirm that tidal marshes similar to the one tested in this study are highly erosion resistant with low erodibility. More research is necessary to confirm this for tidal marshes with different soil and vegetation properties. For tidal marshes similar to what is tested thus far, erosion under dike breach conditions is negligible and other erosion mechanisms such as headcut erosion probably dominate the erosion process.